Dual‐Mode Calixarene‐Based Chemosensor: Highly Selective Fluorogenic Detection of Hg2+ and Chromogenic Detection of Cu2+ with a Single Ionophore. Issue 2 (27th December 2018) - Patra, Subrata; Boricha, Vinod P.; Paul, Parimal
Abstract : A fluorescent molecular sensor has been synthesized incorporating a Re I ‐bipyridine moiety as a fluorogenic unit and amide‐incorporated modified calix[4]arene as recognition moiety. This molecule behaves as a dual sensor, it exhibited highly selective turn‐on fluorescent sensing for Hg 2+ and naked eye colourimetric detection of Cu 2+ over a wide range of metal ions. The ion‐competition study revealed no significant interference from any other metal ion used in this study. Mechanistic studies revealed that the combination of soft (nitrogen) and hard (oxygen) donors in the large and flexible macrocyclic coordination site promoted interaction of Hg 2+ with nitrogen atoms, which perturbed the fluorescence properties of the molecule restricting the PeT process, and the coordination of Cu 2+ with oxygen atoms resulted in new ICT absorption band in the visible region triggering color change. This is a rare example, particularly with calixarene, where a single receptor exhibited dual‐mode selectivity in different sensing channels. Abstract : A new calixarene‐based molecular sensor has been developed, which exhibits high selectivity for Hg 2+ in the luminescence channel (turn‐on) and for Cu 2+ in the UV‐Vis channel with sharp colour change. A combination of soft and hard donor atoms in the flexible macrocyclic coordination site promoted the dual‐mode of coordination with different metal ions.